Flexible Electronics: Soft Material‐Enabled, Active Wireless, Thin‐Film Bioelectronics for Quantitative Diagnostics of Cervical Dystonia (Adv. Mater. Technol. 10/2019). Issue 10 (10th October 2019) - Kwon, Young‐Tae; Lee, Yongkuk; Berkmen, Gamze Kilic; Lim, Hyo‐Ryoung; Scorr, Laura; Jinnah, Hyder A.; Yeo, Woon‐Hong
Abstract : In article number 1900458, Woon‐Hong Yeo, Young‐Tae Kwon, Yongkuk Lee, and co‐workers present a soft material‐enabled wireless electronic system that incorporates a nanomembrane wireless circuit and functional chip components, enclosed by an elastomeric membrane. The bioelectronic system offers a gentle, seamless mounting on the skin, while offering a comfortable, highly sensitive and accurate detection of head movements for quantitative diagnostics of cervical dystonia. The full caption text has been replaced. The caption initially published was incorrect and was corrected on 29 October 2019.